Imaging modalities for biological and preclinical research. a compendium - Walter, Andreas; Mannheim, Julia; Caruana, Carmel J. (IOP (Series). Release 21., 2021)
The relentless pace of innovation in biomedical imaging has provided modern researchers with an unprecedented number of techniques and tools to choose from. While the development of new imaging techniques is vital for ongoing progress in the life sciences, it is challenging for researchers to keep pace. Imaging Modalities for Biological and Preclinical Research is designed to provide a comprehensive overview of currently available biological and preclinical imaging methods, including their benefits and limitations. Experts in the field guide the reader through both the physical principles and biomedical applications of each imaging modality, including description of typical setups and sample preparation. Volume 2 focuses on in vivo imaging methods, including intravital microscopy, ultrasound, MRI, CT and PET. Correlative multimodal imaging, (pre)clinical hybrid imaging techniques and multimodal image processing methods are also discussed. The volume concludes with a look ahead to emerging technologies and the future of imaging in biological and preclinical research. Part of IPEM-IOP Series in Physics and Engineering in Medicine and Biology.